191 THE DEVELOPMENT OF A COGNITIVE COMMUNICATION PROGRAMME FOR OLDER PERSONS IN THE EARLY STAGES OF REDUCED COGNITIVE FUNCTION. (25th October 2022) - McCusker, C; Cawley, T; Cannon, E; Cullen, C
Abstract: Background: Research indicates that cognitive and language stimulation activities can promote the maintenance of skill set. The Speech and Language and Occupational Therapy Service on an Integrated Care Team for the Older Person's and Reablement team developed and implemented a six-week cognitive communication stimulation programme aimed at targeting cognitive and communication functions in older people in the early stages of cognitive decline. The programme outline targeted the following four domains: Memory, Attention, Language and Problem Solving. These areas have been identified as imperative skills for successful engagement and communication in everyday tasks. It was developed during the pandemic with an awareness of the social isolation and reduced opportunity for engaging with cognitive and language activities for older persons locally. Methods: The programme was targeted within the person's home in order to optimise the best outcomes for generalisation of skills. The implementation of the programme was supported by therapists and therapy assistants. The impact of the project was measured by a 10-point scale targeting the Older Person's perceived skills in each cognitive domain pre and post programme implementation. The Mini-Cog was also completed pre and post-programme implementation. Results: Preliminary results from 20 participants demonstrated positive outcomes for older persons who engaged in the programme. Older persons' reported feeling more confident in managing the skills required to maintain cognitive functions. Conclusion: Cognitive and language stimulation activities can support the maintenance of cognitive skills when targeted in the early stages of cognitive decline. There is a greater likelihood of skill maintenance when targeted within the person's home context.